Etnologické modely a proces neolitizace na Předním východě - Šárka Velhartická (AntropoWebzin, 2014)
The study of the origin and the process of neolitisation of the Near East remains a dynamically developing discipline. The newest archaeological finds in this area reveal records of the transformations of early neolithic society not only from the materialistic, but also from social and religious perspectives. Since the 1960s the advent of processual archeology and ethnoarchaeology resulted in archaeology using ethnological materials to a greater extent in interpreting archaeological finds. However, the often imprecise applications of the models and controversial interpretations resulted in a confrontation and crisis in the study of hunter-gatherer societies at the turn of the 1980s and 1990s. A reappraisal of the interplay of both disciplines resulted.